2017
DOI: 10.3390/cells6040040
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren’s and Ledderhose Diseases in a Family with LMNA-Related Cardiomyopathy and a Novel Variant in the ASTE1 Gene

Abstract: Dupuytren’s disease (palmar fibromatosis) involves nodules in fascia of the hand that leads to flexion contractures. Ledderhose disease (plantar fibromatosis) is similar with nodules of the foot. While clinical aspects are well-described, genetic mechanisms are unknown. We report a family with cardiac disease due to a heterozygous LMNA mutation (c.736C>T, p.Gln246Stop) with palmar/plantar fibromatosis and investigate the hypothesis that a second rare DNA variant increases the risk for fibrotic disease in LMNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…However, majority of the LMNA-CM individuals are below the trend-line, which explains the aggregated average percent defective for LMNA-CM and LMNA-CM-A groups. From clinical data [ 4 , 9 , 10 ], we knew that the older patients in the cohort (LMNA-CM) developed heart disease later in life. Therefore, we plotted the difference between each patient’s cells’ dysmorphic nuclei percentage and the predicted value based on the control trend line (green arrow, Fig 4A ) against the age at which patients first presented with heart disease symptoms ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, majority of the LMNA-CM individuals are below the trend-line, which explains the aggregated average percent defective for LMNA-CM and LMNA-CM-A groups. From clinical data [ 4 , 9 , 10 ], we knew that the older patients in the cohort (LMNA-CM) developed heart disease later in life. Therefore, we plotted the difference between each patient’s cells’ dysmorphic nuclei percentage and the predicted value based on the control trend line (green arrow, Fig 4A ) against the age at which patients first presented with heart disease symptoms ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Human fibroblast cells were collected from three families with different mutations of heterozygous LMNA splice-site mutation (c.357-2A>G) [ 4 ] (Family A); LMNA nonsense mutation (c.736 C>T, pQ246X) in exon 4 [ 10 ] (Family B); LMNA missense mutation (c.1003C>T, pR335W) in exon 6 [ 9 ] (Family C). Moreover, related individuals’ fibroblast cells in each family were collected as mutation-negative controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family studies have revealed that there is a genetic component with manifestation of palmar and plantar fibromatosis. Zaragoza et al described the novel co-occurrence of palmar and plantar fibromatosis and LMNA-related cardiac disease in a family with a previously described nonsense mutation, LMNA c.736C>T (p. Gln246Stop) [32]. A novel, heterozygous missense variant (c.230T>C, p. Val77Ala) in the Asteroid Homolog 1 (ASTE1) gene has been revealed as a potential risk factor in fibrotic disease [32].…”
Section: Clinical Appearancesmentioning
confidence: 99%
“…Zaragoza et al described the novel co-occurrence of palmar and plantar fibromatosis and LMNA-related cardiac disease in a family with a previously described nonsense mutation, LMNA c.736C>T (p. Gln246Stop) [32]. A novel, heterozygous missense variant (c.230T>C, p. Val77Ala) in the Asteroid Homolog 1 (ASTE1) gene has been revealed as a potential risk factor in fibrotic disease [32]. They suggest that ASTE1 may contribute to the increased risk for palmar/plantar fibromatosis in patient with Lamin A/C haploinsufficiency [32].…”
Section: Clinical Appearancesmentioning
confidence: 99%